(untitled) (Politeja, 2019)
By all accounts, the Islamic Republic of Pakistan has the strictest “blasphemy laws” among countries with a majority Muslim population. The controversial amendments to the provisions of the Pakistan Penal Code on “offences relating to religion” go back to General Zia ul-Haq’s top-down policies of Islamization. Despite their flaws, doubtful legitimacy, and negative repercussions, the “blasphemy laws” have neither been reformed nor abolished under subsequent governments. This contribution will shed light on the complex political, economic, and social factors that have led to both the emergence of the laws and to the continuous escalation of the situation in terms of increased sectarian and religiously- motivated violence that the ongoing debate about the “blasphemy laws” has engendered. It may be asked, to what extent the controversy on the laws can be taken as indicative of problems with which the country was confronted since its formation, and to what extent shifts and transformations in the socio-political structure of Pakistan, the inability or unwillingness of the authorities to deal with the challenges in a systematic way, and also external factors have exacerbated these deep-rooted problems.